2009
DOI: 10.3149/jms.1603.316
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role Orientation and Relational Closeness: Self-Disclosive Behavior in Same-Sex Male Friendships

Abstract: Although the nature of intimacy within same-sex male friendships exhibits a marked difference from that of same-sex female friends, the open sharing of the self (known as self-disclosure) does occur regularly among male friends, albeit to a varying degree. The present research looks at the relationship between gender role orientation and self-disclosive behavior, empirically confronting the cultural stereotype that the enactment of self-disclosure is gendered. Most significantly, the present research looks at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…"The open sharing of the self (self-disclosure) does occur regularly among male friends, albeit to a varying degree." [39]. Specific elements of self-disclosure that may be important are the amount of personal information revealed, control over the conversational circumstances, topical breadth, and the emotional valence of the personal material disclosed.…”
Section: Discussionmentioning
confidence: 99%
“…"The open sharing of the self (self-disclosure) does occur regularly among male friends, albeit to a varying degree." [39]. Specific elements of self-disclosure that may be important are the amount of personal information revealed, control over the conversational circumstances, topical breadth, and the emotional valence of the personal material disclosed.…”
Section: Discussionmentioning
confidence: 99%
“…After several years of being friends, it may be that any issues of homophobia or non-normative masculine behavior have long since been resolved and no longer have much salience in these well-established friendships where presumably, both men know each other well and feel comfortable and secure in each other's presence (Hall, 2011). If men in the initial stages of same-sex friendship development had been included in the current study, issues of masculine norms and homophobia might have produced a much stronger effect on friendship quality because these men would not have had the time to negotiate the effects of uncertainty generated by these issues (Bowman, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, researchers have demonstrated that in men's same-sex friendships, self-disclosure is positively associated with closeness (Bowman, 2008), relational satisfaction (Meeks, Hendrick, & Hendrick, 1998), relational stability (Sprecher, 1987), and feelings of love and commitment (Sprecher & Hendrick, 2004). Reisman (1990) found that greater amounts of self-disclosure lead to greater friendship satisfaction in men, while Bank (1995) reported a positive association between frequent expressive behaviors in best same-sex male friendship and more enjoyment of the friendship.…”
Section: Homophobia and Men's Same-sex Friendshipsmentioning
confidence: 99%
See 2 more Smart Citations